Whole blood platelet aggregation determined by the ROTEM platelet equipment; reference intervals and stability. (17th February 2020) - Nissen, Peter H.; Skipper, Mette Tiedemann; Hvas, Anne-Mette
Abstract: Point of care testing of residual effect of antiplatelet therapy in trauma patients or during major surgery may result in improved clinical management of significant bleeding. We included 121 healthy individuals (57 females and 64 males, aged 22–65 years) in order to establish reference intervals for platelet aggregation induced by adenosine diphosphate (ADPTEM, 10 µM), arachidonic acid (ARATEM, 0.42 mM) and thrombin activating peptide (TRAPTEM, 36 µM) employing the ROTEM platelet module. Further, the impact of citrate (3.2%) and hirudin (>15 µg/ml) as anticoagulants was evaluated. Finally, we investigated assay stability (15, 30, 60, and 120 min after blood sampling) (n = 8) and between-day variation (n = 5). We report reference intervals for 121 healthy individuals and reference intervals by gender. We observed significantly higher platelet aggregation in females than in males (all P -values < 0.05). No correlation between age and platelet aggregation was observed, except for the parameter TRAPTEM amplitude (A6), in which a decline in A6 was observed with increasing age ( P = 0.03). We observed significantly lower levels of platelet aggregation in citrate tubes than in hirudin tubes (all P -values < 0.05), except from TRAPTEM maximum slope, where no significant difference was observed ( P = 0.40). The stability was acceptable (≤20% deviation) for up to 120 min for ARATEM in citrate tubes, and up to 60 min for the ADPTEM and TRAPTEM assays in citrate tubes. In hirudin tubes we found ADPTEM and ARATEM assays to be stable for 60 min, while the stability of TRAPTEM in hirudin tubes was found to be stable for 30 min. Using citrate tubes, the between-day variation (mean coefficient of variation, CV) was 19–20% for ADPTEM, 19–26% for TRAPTEM, and 10% for ARATEM, whereas the mean CV was 11–13% for all three assays in hirudin tubes. In conclusion, we established combined and gender-specific reference intervals for three platelet aggregation assays in both citrate- and hirudin tubes. In citrate tubes, the stability of the ROTEM platelet assays was 60–120 min, while the stability in hirudin tubes was 30–60 min. The between-day variation was lowest for samples obtained in hirudin tubes.